Mini-review: research and progress of oxeiptosis in diseases - Chen, Ke-Qian; Wang, Shu-Zhi; Lei, Hai-Bo; Liu, Xiang (Frontiers in Cell and Developmental Biology, 2024)
Oxeiptosis is a novel cell death pathway that was introduced in 2018. As a form of regulated cell death, it operates independently of caspases and is induced by ROS.Distinguished from other cell death pathways such as apoptosis, necroptosis, pyroptosis, and ferroptosis, oxeiptosis features unique damage causes (ROS), pivotal genes, and signaling pathways (KEAP1/PGAM5/AIFM1). Emerging studies indicate that oxeiptosis plays a significant role in the progression of various diseases and its regulation could serve as a promising therapeutic target. However, the precise molecular mechanisms underlying oxeiptosis remain to be fully elucidated. In this mini-review, we systematically summarize the latest developments in oxeiptosis-related diseases while detailing the molecular mechanisms and regulatory networks of oxeiptosis. These insights offer a foundation for a deeper understanding of oxeiptosis.